IFPRI Kenya strengthens impact evaluation capacity at the University of Nairobi - Ayalew, Hailemariam; Kimaiyo, Faith Chepkemoi; Gituro, Sam; Kramer, Berber; Karachiwalla, Naureen; Breisinger, Clemens (CGIAR System Organization, 2024)
From October 1st to 3rd, 2024, the International Food Policy Research Institute (IFPRI) Kenya office organized a transformative training on Impact Evaluation for teaching staff at the University of Nairobi. Led by Dr. Hailemariam Ayalew Tiruneh, Dr. Berber Kramer, and Dr. Naureen Karachiwalla, this initiative was a significant step in strengthening the capacity of local partners to conduct evidence-based research and foster accountability in development. This is part of a continued collaboration between the University of Nairobi, IFPRI and the CGIAR Initiatives on National Polices and Strategies (NPS).